2020
DOI: 10.1016/j.ebiom.2020.102647
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of tumor necrosis factor receptor TNFRSF9 (4-1BB) DNA methylation with regard to molecular and clinicopathological features, immune infiltrates, and response prediction to immunotherapy in melanoma

Abstract: Background: Immunotherapy, including checkpoint inhibition, has remarkably improved prognosis in advanced melanoma. Despite this success, acquired resistance is still a major challenge. The T cell costimulatory receptor TNFRSF9 (also known as 4-1BB and CD137) is a promising new target for immunotherapy and two agonistic antibodies are currently tested in clinical trials. However, little is known about epigenetic regulation of the encoding gene. In this study we investigate a possible correlation of TNFRSF9 DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 88 publications
0
49
0
Order By: Relevance
“…Thus, DNA methylation-based biomarkers have been extensively studied for predicting prognosis and response to conventional therapy [11,12]. Silenced immune-related genes by promoter hypermethylation have been recently found to be predictive of ICB therapy response [13][14][15]. Given that the loss of functions in immune-related genes by genomic mutations (e.g., truncating mutations and copy number deletion) account for primary and acquired resistance to ICB therapy [16][17][18], we hypothesize that the silencing of immune genes through promoter hypermethylation could be one of the key mechanisms resulting in immune evasion.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, DNA methylation-based biomarkers have been extensively studied for predicting prognosis and response to conventional therapy [11,12]. Silenced immune-related genes by promoter hypermethylation have been recently found to be predictive of ICB therapy response [13][14][15]. Given that the loss of functions in immune-related genes by genomic mutations (e.g., truncating mutations and copy number deletion) account for primary and acquired resistance to ICB therapy [16][17][18], we hypothesize that the silencing of immune genes through promoter hypermethylation could be one of the key mechanisms resulting in immune evasion.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic alterations, however, have widely been neglected as potential predictive biomarkers so far but have great potential due to their significance in tumorigenesis and immunology, including immune cell differentiation and T cell exhaustion [8][9][10][11][12]. Recent reports suggest DNA methylation of genes encoding for the immune checkpoints 4-1BB, LAG-3, PD-L2, and CTLA-4 as predictive biomarkers for response to ICB in melanoma [13][14][15][16]. Our present study aimed at the analysis of the value of CTLA4 methylation as a biomarker to predict response and progression under CTLA-4-directed ICB monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Among the immune-related genes co-expressed with KIF20A, many genes are closely related to immune cells. For example, Bartkowiak and their colleagues found that TNFRSF9 that expressed on both T cells and antigen-presenting cells, could enhance the effect of activated T cells, further increasing of cytokines and TIL expansion (21). Klement et al detected that immune checkpoint CD44 could activate multiple cell signaling pathways, thereby a series cell activity inducing cell proliferation, cell survival, cytoskeletal changes and cell motility (22).…”
Section: Discussionmentioning
confidence: 99%